Relationship between body condition score on the service per conception and conception rate of Brahman Cross cows - Ervandi, Mohamad; Ihsan, Moh. Nur; Wahjuningsih, Sri; Anugra Yekti, Aulia Puspita; Susilawati, Trinil (Faculty of Animal Science, Universitas Brawijaya, 2020)
The factors that influence the success of Artificial Insemination is affected by acceptors that will be used for AI which have a good Body Condition Score, because BCS has a relationship with animal reproduction, such as fertility and pregnancy. The purpose of this research was to evaluate and determine the relationship of Body Condition Score (BCS) on Service per Conception (S/C) and Conception Rate (CR). The material used was 80 Brahman Cross (BX) cows, the sample was selected by Purposive Sampling with the criteria 2-3 years old with body weight ranged from 300-500 kg, gave birth, and BCS between 4-7 (scale 1-9). The method used in this study was the survey method. The variables observed were the relationship between Body Condition Score (BCS), Service per conception (S/C), and Conception Rate (CR). The data was obtained by using correlation analysis and also a simple regression with the SPSS 2.0 software program, then analyzed descriptively. The results showed that the equation of relationship between BCS and S/C variables obtained r = 0.961% and the regression value equation y = -25.998 + 1.520x (R2) 23.9%. The relationship between BCS and CR variables obtained a value of r = 0.976% and BCS regression equation value with CR y = -39.727 + 1.109x (R2) 29.5%. The research thus concludes that there is a positive relationship that is being between BCS on the S/C and CR of Brahman Cross cows.